The Influence of Price, Health Concern, and Customer Experience on Repurchase Intention of Mouthwash Products Post-Pandemic Period - Agil Pratama; Megawati Simanjuntak; Nur Hasanah (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The end of COVID-19 pandemic has led to a nationwide decline in mouthwash sales.Purpose: This study aims to analyze the influence of price, health concern, and customer experience identified as key factors impacting repurchase intention.Design/methodology/approach: An online survey was conducted with 219 respondents who met the criteria. Data were analyzed using SEM PLS approach through SmartPLS 3.0 software. The study examined the relationships between price, health concern, and customer experience on repurchase intention, with purchase behavior as a mediating variable.Findings/Result: The findings revealed that price, customer experience, and purchase behavior significantly influence repurchase intention. Additionally, health concern significantly impacts purchase behavior.Conclusion: Based on these findings, mouthwash manufacturers are encouraged to implement value-based pricing strategies to strengthen consumers’ perceived value, enhance sensory customer experiences through innovative product development, promote purchase behavior by bundling products with other relevant household items, and optimize health concern by utilizing consumer testimonials and health case studies to build trust in product benefits.Originality/value (State of the art): The uniqueness of this study lies in the integration of the customer experience variable with a sensory approach in the context of repurchasing everyday health products, which has not been extensively explored. Keywords:   mouthwash, pandemic covid-19, repurchase intention, stretegic, sem pls